Težave na področju govorno-jezikovne komunikacije pri šolskih otrocih ter uporaba spletnih in mobilnih orodij - Jelenc, Nika (Rehabilitacija (Ljubljana), 2018)
Background: Speech, language and communication (SLC) play an essential role in acquiring academic skills. In the framework of the Erasmus+ project Speech and Language Pathology Interactive Tools for Teachers at Initial Education (No. of contract 2017-1-BG01-Ka201-036295), we conducted a survey in the academic year 2017/2018. Our goal was to determine how many children, from the standpoint of school teachers and guidance counsellors, have difficulties with SLC, in which areas are the difficulties most frequent, and the extent of teachers' and counsellors' interest for the use of online and mobile tools that enable identification of SLC difficulties and support development of children's SLC skills. Methods: Eighteen counselling and 45 educational workers from various elementary schools across Slovenia participated in the study, who answered questions of an online questionnaire on the SurveyMonkey platform during February 2018. Results: In the opinion of teachers and counsellors in children aged 6 to 12, difficulties with language understanding prevail, which are expressed in about one fifth of the children taught by teachers and about one half of the children who are being consulted by counsellors. The participants are generally confident that the number of children with SLC difficulties is increasing. The use of online and mobile tools to identify SLC difficulties and develop SLC skills among children by teachers and counsellors is rare, mainly because of their unfamiliarity. Interest and expectations for the development of such mobile tools, on the other hand, are high. Conclusion: According to the teachers' and counsellors' perception of the increasing trend of children's SLC difficulties, the research confirms the importance of the development of mobile tools, especially tools for developing SLC skills in children.
Keywords: child; mobile and online tools; mobilna in spletna orodja; motnje govora; otrok; rehabilitacija; rehabilitation; Rehabilitation of Speech and Language Disorders; speech disorders; vocational rehabilitation